Neuromodulation of the Dorsal Root Ganglion for Chronic Postsurgical Pain. (1st June 2019) - Antony, Ajay B; Schultheis, B Carsten; Jolly, Suneil M; Bates, Daniel; Hunter, Corey W; Levy, Robert M
Abstract: Objective: The objective of this study is to review the available evidence for dorsal root ganglion (DRG) stimulation for the treatment of complex regional pain syndrome type II (CRPS II; peripheral causalgia) associated with chronic neuropathic postsurgical pain (NPP). Design: Available literature was identified through a search of the US National Library of Medicine's Medline database, PubMed.gov. References from published articles also were reviewed for relevant citations. Results: The data published to date support the use of DRG stimulation to treat chronic NPP of the groin, knee, and foot. NPP following procedures such as thoracotomy, hernia surgery, and knee replacement surgery were identified as some of the conditions for which DRG stimulation is likely to be effective. Conclusion: DRG stimulation is known to be an effective treatment for focal neuropathic pain. Currently, NPP of the foot, groin, and knee all appear to be the conditions with the most clinical experience, backed by a limited but growing body of evidence. However, prospective studies lag behind real-world clinical experience and are needed to confirm these findings.